An Analysis of Translation Challenges in ESP Programs: A Rubric-Based Evaluation of Polytechnic Students’ Performance - Romadloni, Annisa; Sari, Laura (Universitas Kristen Cipta Wacana, 2025)
This study investigates the translation challenges faced by students enrolled in English for Specific Purposes (ESP) programs at polytechnic institutions. Recognizing that translation tasks demand both linguistic and technical competencies, this research aims to assess students’ translation performance across four key criteria: accuracy, grammar, fluency, and adherence to meaning. Employing a mixed-methods approach, fifteen students were assigned to translate technical and narrative texts commonly found in ESP curricula. Their translations were evaluated using a rubric-based system to identify patterns in performance and recurring issues. The results show that while most students demonstrated high levels of accuracy and adherence to meaning, several faced difficulties in grammar and fluency, particularly when translating culturally rich or narrative content. These findings highlight the importance of integrating targeted translation training into ESP courses, with a focus on enhancing grammatical precision and natural language flow. The study contributes to a better understanding of how polytechnic students translate specialized texts and offers practical recommendations for improving translation instruction within ESP frameworks.